Representatif Kolonialisme dalam Novel Laskar Pelangi Karya Andrea Hirata: Pendekatan Sosiologi Sastra dan Teori Postkolonialisme - Azzahra, Ratna; Nurholis, Nurholis (Suara Bahasa, 2023)
This research applies qualitative research methods with a sociological literary approach supported by postcolonialism theory to analyze the novel "Laskar Pelangi" by Andrea Hirata. The novel portrays the impact of Dutch colonialism in Indonesia and highlights resistance against it. The research focuses on the representation of local culture in the novel, emphasizing the cultural richness and the characters' struggle to maintain their identity. The author, having personal experience in an area affected by colonialism, provides an authentic perspective on the effects of colonialism and the struggles of the community. Through the sociological literary approach, the research examines the social, cultural, and political dynamics in the context of colonialism. The research also highlights the use of language in the novel, which reflects linguistic diversity and the rejection of colonial language dominance. The findings of this research deepen our understanding of the impact of colonialism, resistance against it, and the role of local culture in preserving identity. This research contributes to the understanding of colonial oppression systems and the challenges faced by communities in preserving their cultural identity. By combining qualitative methods, sociological literary approach, and postcolonialism theory, this research offers a broader perspective on the complexity of colonial experiences and challenges existing colonial norms. In conclusion, this research encourages readers to question oppressive systems within their own environments and celebrate cultural diversity and resistance against colonial domination. Keywords: Postcolonialisms, Laskar Pelangi. Sociology Literature